SAT0054 The Body Mass Index and Its Influence on the Activity of Rheumatoid Arthritis: Results from the QUEST-RA Study Morocco. (23rd January 2014) - Ezzahri, M.; Amine, B.; Hajjaj-Hassouni, N.; Benchakroun, B.; Benbrahim, L.; Ahid, S.
Abstract : Background: The results of the international QUEST RA study showed that the high BMI was associated with a high activity of rheumatoid arthritis (RA) in women. Althoughour country is in developing, 25, 2 % of the population is in overweight and 10, 3% are obeses. Objectives: The aim of our study was to analyze the relationship between body mass index (BMI) and the activity of rheumatoid arthritis in Moroccan population. Methods: This is a multicenter cross-sectional study, conducted between December 2008 and May 2010, involving patients with rheumatoid arthritis in the QUEST-RA program of Morocco. The clinical and demographic data were collected by rheumatologists in the public and liberal sectors. The disease activity was assessed by clinical examination, ESR, CRP and DAS28. The functional impact was evaluated by the HAQ. BMI was stratified according to the Clinical Guidelines on the Identification, Evaluation, and Treatment of Overweight and Obesity in Adults established in 1998, as follows: underweight <18.5, normal weight: 18.5 to 24.9, overweight: 25 to 29.9 and obesity> or = 30. Results: 1129 patients were included, the mean age was 48.82 ± 12.71 years. Among our patients, 441 (42%) were overweight, 389 (37%) were normal weight, 186 (17.7%) were obese, and 35 (3.3%) in a state of underweight. The mean DAS28 was 4.93 ± 1.68. The mean score for DAS28 decreased with BMI; underweight (5.76 ± 1.41), normal (5.02 ± 1.75) in overweight (4.89 ± 1.58) and obesity (4.82 ± 1.58) in women, whereas the opposite trend was observed in men. The analysis of variance (ANOVA) did not detect a statistically significant relationship between the different categories of BMI and DAS28; underweight (ANOVA: p = 0.13), normal (p = 0.48), overweight (p = 0.29), obesity (p = 0.24). Conclusions: The body mass index with its differents categories does not seem to be related to disease activity assessed by the DAS28 in Moroccan patients with RA, contrary to whatwas found onthe international QUEST-RA study. Disclosure of Interest: None Declared